Airplane headache - an underestimated problem? - Marcin Kulczyński; Michał Marciniec; Klaudia Sapko; Ewa Papuć; Konrad Rejdak (Kazimierz Wielki University, 2018)
The airplane headache is an incident of severe, clinically stereotypical pain during ascent or descent of an airplane. The entity is considered rare; however, growing numer of passengers in air transport results in better recognition of the problem. The airplane headache typically lasts less than 30 minutes and is unilateral, most often in fronto-orbital region and is connected with take-off or (more often) landing of the aircraft. The most important causative factor is sinus barotrauma attributed to changes in air pressure in passenger airliners during different phases of flight. So far there are only single cases or case series described in the literature. However, the problem can affect even a few percent of airline passengers. The condition is rare among children. The most effective treatment are triptans, but naproxen, paracetamol and nasal decongestants may play an important role either. There is an urgent need to conduct more researches on epidemology, pathogenesis and treatment of the headache attributed to airplane travel.